Absolute Quantitative Lipidomics Reveals Differences in Lipid Compounds in the Blood of Trained and Untrained Yili Horses - Tongliang Wang; Jun Meng; Jianwen Wang; Wanlu Ren; Xixi Yang; Wusiman Adina; Yike Bao; Yaqi Zeng; Xinkui Yao (Veterinary Sciences)
The purpose of this study was to explore the relationship between blood lipid levels and the differences in cardiac structure and function of trained and untrained Yili horses as related to exercise performance. We utilized quantitative lipidomics technology to elucidate how the differences in lipid compounds in the blood influenced performance outcomes. Sixteen 18-month-old Yili horses were selected, ten of which received a 15-week training regimen, and six were kept as untrained controls. Cardiac structure and function were assessed by echocardiography, while plasma lipid metabolites were detected and identified by liquid chromatography–mass spectrometry. The results showed that key cardiac structural indices, such as left ventricular end-diastolic diameter, left ventricular end-systolic diameter, and left ventricular posterior wall thickness, were significantly greater in the trained group compared with the untrained group, indicating that exercise training promotes adaptive cardiac remodeling. Regarding lipid metabolites, significant differences were observed between the trained and untrained groups, with a total of 281 lipids identified—212 upregulated and 69 downregulated. These differentially expressed lipids were primarily enriched in pathways such as necroptosis, ether lipid metabolism, and sphingolipid signaling, which are associated with cell migration, survival, proliferation, and regulation of lipid metabolism. Further correlation analysis revealed that differences in certain lipids, such as PE (20:4_18:0), PC (17:0_18:1), and LPC subclasses, were significantly correlated with exercise-mediated cardiac structural and functional changes and exercise performance enhancement. These findings provide novel molecular insights into the effects of exercise training on cardiac structure and lipid metabolism in horses and can serve as a reference for training strategies and preserving cardiac health in performance horses.